Clinical and radiological outcome of incidental cerebral small vessel disease using antiplatelet therapy: randomized pilot study - Yasmine Hassan Abdelhamid; Eman Hamid; Mena Elerian; Hossam Shokri; Mai Fathy; Tamer Roushdy; Hani Zakieldine; Nevine El Nahas; Hany Aref (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Cerebral small vessel disease (CSVD) causes significant disability at increasing age, such as cognitive impairment, gait, and sphincteric problems affecting a person’s quality of life. That is why it is essential to be detected and managed early. The aim of this study is to investigate clinical and radiological progression among a sample of Egyptian patients with incidental CSVD after a 1-year antiplatelet therapy, either aspirin or cilostazol. Results Regarding the MRI lesions, both visual rating scales and lesion load assessment did not show any significant difference between baseline and follow-up. As for the clinical assessment, there was also no significant difference between the two groups at baseline and follow-up. Conclusion Neither aspirin nor cilostazol had an impact on clinical and radiological progression over 1 year in patients with CSVD. More sophisticated tools are needed to assess radiological progression in CSVD. The trial is registered in PACTR No. PACTR202301861240705. https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=19331 . Date of Approval: 31/1/2023.